LncRNAs Landscape in the patients of primary gout by microarray analysis - Qing, Yu-Feng; Zheng, Jian-Xiong; Tang, Yi-Ping; Dai, Fei; Dong, Zeng-Rong; Zhang, Quan-Bo (PloS one, 2021)
To determine the expression profile and clinical significance of long non-coding RNAs (lncRNAs) in peripheral blood mononuclear cells (PBMCs) of patients with primary gout and healthy control subjects. Human lncRNA microarrays were used to identify the differentially expressed lncRNAs and mRNAs in primary gout patients (n = 6) and healthy control subjects (n = 6). Bioinformatics analyses were performed to predict the roles of differently expressed lncRNAs and mRNAs. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to detect the expression levels of 8 lnRNAs in 64 primary gout patients and 32 healthy control subjects. Spearman’s correlation was used to analyze the correlation between these eight lncRNAs and the laboratory values of gout patients. A receiver operating characteristic (ROC) curve was constructed to evaluate the diagnostic value of the lncRNAs identified in gout. The microarray analysis identified 1479 differentially expressed lncRNAs (879 more highly expressed and 600 more lowly expressed), 862 differentially expressed mRNAs (390 more highly expressed and 472 more lowly expressed) in primary gout (fold change > 2, P < 0.05), respectively. The bioinformatic analysis indicated that the differentially expressed lncRNAs regulated the abnormally expressed mRNAs, which were involved in the pathogenesis of gout through several different pathways. The expression levels of TCONS_00004393 and ENST00000566457 were significantly increased in the acute gout flare group than those in the intercritical gout group or healthy subjects (P<0.01). Moreover, inflammation indicators were positive correlated with TCONS_00004393 and ENST00000566457 expression levels. The areas under the ROC curve of ENST00000566457 and NR-026756 were 0.868 and 0.948, respectively. Our results provide novel insight into the mechanisms of primary gout, and reveal that TCONS_00004393 and ENST00000566457 might be as candidate targets for the treatment of gout flare; ENST00000566457 and NR-026756 could effectively discriminate between the gout and the healthy control groups.